Pengaruh Brand Image, Brand Luxury , Harga, Dan Desain Produk Terhadap Minat Beli Samsung Z Flip 5 Di Kota Semarang - Naim, Aulia Anin; Sedayu, Agung; Usman, Usman; Hariyadi, Guruh Taufan (Politeknik Negeri Ambon, 2024)
This research aims to determine the influence of brand image, luxury brand, price, and product design on buying interest in the Samsung Z Flip 5 in Semarang City. This research uses primary data and quantitative methods. Researchers conducted a pre-survey on 30 respondents by distributing questionnaires, then after that the researchers conducted a survey by distributing questionnaires via Google Form to 150 respondents and processing the data using SmartPLS. From the results of data processing, it was found that brand image had a significant influence, luxury brand had no significant influence, price had a significant influence, and design had no significant influence on interest in purchasing Samsung Z Flip 5 smartphone products in Semarang City. Â Keywords: Â Brand Image ; Brand Luxury ; Price ; Design ; Purchase Intention